Comparison of seven cyclosporine A formulations for dry eye disease: A systematic review and network meta-analysis - Gao, Dongyang; Da, Zhuoli; Yang, Kan; Shi, Yuanyuan (Frontiers in Pharmacology, 2022)
Abstract Background: Dry eye disease is a common ocular surface disease affecting tens of millions of people worldwide. It is characterized by an unstable tear film and increasing prevalence. Different commercial formulations of cyclosporine A for dry eye have been approved ，however, it is still unclear whether the differences in formulations of these products will make a difference in clinical efficacy and safety. Methods: Randomized controlled trials of commercial cyclosporine A formulation for dry eye disease were searched in Pubmed, EMBASE, Scopus, and Cochrane controlled trials registries and Web of Science from inception till 1 Dec 2021. Independent literature screening, data extraction, quality evaluation, and the study in line with quality standards were analyzed by using Stata16.0 software. The study is registered with PROSPERO under the number CRD42022301423. Code and data for this study is publicly available (https://github.com/DongYangGao/Dongyang.github.io.git). Results: 21 randomized clinical trials with a total of 4107 participants were included in this study. Restasis® (OR-4.82, 95% CI-6.18 to 3.45, SUCRA 77.2%) was the most effective commercial formulation for reducing OSDI, Zirun® (SUCRA 73.9%) performed better in improving Schirmer’s test. TJ Cyporin® (SUCRA 65.3%) ranked first in terms of improving tear film break-up time. For treatment-emergent adverse events incidence, Clacier® was close to placebo. The risk of reporting bias is considered low. Conclusion: In the comparison of outcomes included in this study, the optimal order of various commercial cyclosporine A formulations is different, so it is difficult to select the optimal formula. Appropriate commercial formulations should be selected according to patients’ conditions in clinical practice.